Parental socialization styles and emotional dependence in 16 to 17-year-old females in national educational institutions in Lima, 2014 - Muñoz Díaz, Zoraida Estefany (2015)
Present study aimed to determine if there is any relation between parental socialization styles and emotional dependence. It was performed following quantitative approach with descriptive correlational purposes and a transversal design. The sample consisted of 211 women, to the ages of 16 and 17 years old, who were in the fourth and fifth grade of secondary in five public high schools from Los Olivos district. The instruments used were Parental Socialization Styles Scale in Adolescence (ESPA 29) and Emotional Dependence Questionnaire (CDE). Results showed there is no a statistically significant relation between parental socialization styles and emotional dependence, however a correlation was found between mother’s parental socialization styles and change of plans dimension (< 0.05). Regarding parental styles, it was found indulgent and authoritarian styles prevail in mothers and a neglectful style in fathers. Besides, 25.6% of the sample reached high levels of emotional dependence.